2015
DOI: 10.1371/journal.pone.0128884
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Photodegradation of Dissolved Organic Matter to Dissolved Inorganic Carbon and Particulate Organic Carbon

Abstract: Photochemical transformation of dissolved organic matter (DOM) has been studied for more than two decades. Usually, laboratory or “in-situ” experiments are used to determine photodegradation variables. A common problem with these experiments is that the photodegradation experiments are done at higher than ambient temperature. Five laboratory experiments were done to determine the effect of temperature on photochemical degradation of DOM. Experimental results showed strong dependence of photodegradation on temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 36 publications
9
34
2
Order By: Relevance
“…For example, we found that contributions of in situ transformation were positively correlated with water temperature (Figures 4C,D). This relationship corresponds with the observed temperature dependence of both bacterial decomposition and Colorado River Decrease in lower section 2300Miller, 2012 photochemical oxidation (Davidson and Janssens, 2006;Porcal et al, 2015)-the two major pathways for in situ DOC loss in aquatic systems (Cole et al, 2007). The lower coefficient of correlation between DOC concentration and temperature in the UMR (4c) was probably due to additional DOC loss pathways, such as sorption onto particles (Aufdenkampe et al, 2001), DOC flocculation (Benedetti et al, 2003) and exchanges with floodplains (Tockner et al, 1999).…”
Section: Tributary Inputs As a Dominant Control On The Doc Longitudinsupporting
confidence: 73%
“…For example, we found that contributions of in situ transformation were positively correlated with water temperature (Figures 4C,D). This relationship corresponds with the observed temperature dependence of both bacterial decomposition and Colorado River Decrease in lower section 2300Miller, 2012 photochemical oxidation (Davidson and Janssens, 2006;Porcal et al, 2015)-the two major pathways for in situ DOC loss in aquatic systems (Cole et al, 2007). The lower coefficient of correlation between DOC concentration and temperature in the UMR (4c) was probably due to additional DOC loss pathways, such as sorption onto particles (Aufdenkampe et al, 2001), DOC flocculation (Benedetti et al, 2003) and exchanges with floodplains (Tockner et al, 1999).…”
Section: Tributary Inputs As a Dominant Control On The Doc Longitudinsupporting
confidence: 73%
“…A sharp decrease in POC concentrations at low salinity has been reported in the Lena delta region and was attributed to sinking of particles (Cauwet and Sidorov, 1996). We speculate that the main drivers on the apparent removal of highly humic content DOM observed within the surface layer are the photodegradation and flocculation, given the high susceptibility of those aromatic carbons to those processes (von Wachenfeldt et al, 2008;Porcal et al, 2013Porcal et al, , 2015Asmala et al, 2014;Helms et al, 2014). Those processes have also been indicated to modulate the non-conservative mixing behavior in other estuaries such as the Mississippi delta (Benner and Opsahl, 2001).…”
Section: Dynamics and Fate Of Dom In The Lena Delta Regionsupporting
confidence: 54%
“…Furthermore, the influence of particulate matter and sediments in coastal and shelf environments has to be taken into account given their influence on DOM removal through the process of sorption and flocculation (Uher et al, 2001;Shank et al, 2005;Guo et al, 2007;Asmala et al, 2014). The flocculation process, in turn, can be increased either due to the presence of the salt in the marine water (Asmala et al, 2014, and references therein) and to the exposition to high light intensities that, together with photochemical processes, can synergistically enhance the DOM removal from the dissolved phase (von Wachenfeldt et al, 2008;Porcal et al, 2013Porcal et al, , 2015. A sharp decrease in POC concentrations at low salinity has been reported in the Lena delta region and was attributed to sinking of particles (Cauwet and Sidorov, 1996).…”
Section: Dynamics and Fate Of Dom In The Lena Delta Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fate of photo-oxidized DOM depends on temperature. For example, at lower temperatures DOM is generally oxidized directly into CO 2 , whereas at higher temperatures DOM is broken into intermediate molecules prior to mineralization into CO 2 (Porcal et al, 2015). In some cases, the alteration of DOM molecular structure via photo-oxidation (e.g., Rodríguez-Zuniga et al, 2008) can result in enhanced biological decomposition (Tranvik and Bertilsson, 2001;Cory et al, 2007Cory et al, , 2014Judd et al, 2007).…”
Section: Estuarine Om Transport Burial and Transformationmentioning
confidence: 99%